Financial market crisis and financial market channel - Bernd Braasch (Intereconomics, 2010)
Before a new financial architecture can be established in the wake of the financial crisis, the increasing importance of the global financial market channel must be fully understood. This importance was illustrated by the unexpectedly strong dampening effects of the financial crisis on the real economy and by the worldwide contagion of the crisis, including its spreading to emerging market economies that were macroeconomically stable. This article argues that the financial sphere is gaining in importance over the real sphere and that the impact of global financial determinants on economic activity is growing ever stronger. The keys to dealing with this change are greater transparency, stronger incentive structures and a stronger regulatory and supervisory framework.
Keywords: 330